A critical review on erosion wear characteristics of polymer matrix composites - Vasavi Boggarapu; Raghavendra Gujjala; Shakuntla Ojha (Materials Research Express, 2020)
Polymer matrix composites (PMCs) are extensively known for their higher strength and stiffness at lower weight compared to traditional materials. They are extensively used in numerous engineering applications. Utilization of these materials had been extended to novel areas where it is essential to study their tribological performance. Several research works reported the tribological performance of polymer composites. The aim of the review is to provide broad information on erosion behaviour of polymeric composites. Attention is paid towards the effect of test parameters i.e. impact velocity, erodent characteristics, impingement angle on the erosion wear rate and their failure mechanisms were discussed. Inclusion of various fillers in to polymeric composites enriched the erosion resistance property that attracted the researchers to find out their application. However limited literature were available on the erosion behaviour of particle filled composites. Hence, another objective is to review available literature on the erosion response of filled composites.